Social Registries for Social Assistance and Beyond : A Guidance Note and Assessment Tool - Leite, Phillippe; George, Tina; Sun, Changqing; Jones, Theresa; Lindert, Kathy (World Bank, Washington, DC, 2017)
This paper makes several contributions. First, it presents a ‘guidance note’ on the framework for Social Registries, anchoring the definition of these systems in their functions along the Delivery Chain and their social policy role as inclusion systems, while clarifying terminology in a manner that is consistent with IT standards in the discussion of their architecture as information systems. Second, it illustrates the diverse typologies and trajectories of country experiences with Social Registries with respect to their (a) institutional arrangements (central and local); (b) use as inclusion systems (coverage, single or multi-program use, static or dynamic intake and registration); and (c) structure as information systems (structure of data management; degree and us of interoperability with other systems). These patterns primarily derive from a review of Social Registries in a sample of 20 countries), (Azerbaijan, Brazil, Chile, China, Colombia, the Dominican Republic, Djibouti, Georgia, Indonesia, Macedonia, Mali, Mauritius, Mexico, Montenegro, Pakistan, the Philippines, Senegal, Sierra Leone, Turkey, and Yemen). The paper also draws on experience in other countries (Kenya, Rwanda, Nigeria, Egypt, Jordan, Vietnam, India, Estonia, Belgium, the US, Canada, Australia, and others) to illustrate specific points. Third, this paper develops a basic ‘Assessment Tool’ covering the core building blocks of Social Registries using a ‘checklist’ style of questions. Given the wide diversity of Social Registries in both their role in social policy and in their architecture, the approach is not prescriptive: it does not advocate for any specific model or blueprint for Social Registries. Any diagnostics or recommendations that emerge from use of this Guidance Note and Assessment Tool will be country specific. Some key take-away messages include: (a) the importance of recognizing both the role of the ‘front lines’ for outreach, intake and registration (Social Registries as inclusion systems) and the ‘back office’ functions of Social Registries as information systems; (b) the potential power of Social Registries as integrated and dynamic gateways for inclusion; (c) the recognition that Social Registries are generally part of end-to-end systems for specific programs, integrated social protection information systems, and/or even ‘whole-of-government’ approaches; and (d) there is significant diversity in the typology and trajectories of Social Registries across countries and over time.